1996
DOI: 10.1046/j.1365-2443.1996.d01-262.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of proteins governing the proteolytic activation of a developmental transcription factor in Bacillus subtilis

Abstract: Background: Spore formation in Bacillus subtilis takes place in a sporangium consisting of two compartments called the forespore and the mother cell. Late in development, when the forespore is wholly contained within the mother cell, gene transcription is coordinated between the compartments by an intercellular signal transduction pathway. This pathway operates at the level of proteolytic processing of the proprotein precursor (pro-¾ K ) to the mothercell transcription factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
113
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 49 publications
(64 reference statements)
9
113
0
Order By: Relevance
“…Mutations in conserved residues in these motifs in SpoIVFB abolished pro-K processing, suggesting that pro-K processing occurs within the membrane (247,311). Consistent with this conclusion, biochemical and cytological experiments have indicated that pro-K , SpoIVFB, SpoIVFA, and BofA all localize to the cell membrane (100,240,249,294,312). Models of how BofA and SpoIVFA effect the negative regulation of SpoIVFB action have undergone a series of changes, perhaps reflecting the complexity of the process (41,100,153,242,249).…”
mentioning
confidence: 59%
“…Mutations in conserved residues in these motifs in SpoIVFB abolished pro-K processing, suggesting that pro-K processing occurs within the membrane (247,311). Consistent with this conclusion, biochemical and cytological experiments have indicated that pro-K , SpoIVFB, SpoIVFA, and BofA all localize to the cell membrane (100,240,249,294,312). Models of how BofA and SpoIVFA effect the negative regulation of SpoIVFB action have undergone a series of changes, perhaps reflecting the complexity of the process (41,100,153,242,249).…”
mentioning
confidence: 59%
“…The anti-SpoIIAA antisera contained antibodies specific for both SpoIIAA and SpoIIAA-P (Diederich et al 1994). Antibodies used in immunofluorescence studies were purified from either crude polyclonal antisera or Protein A purified antibody preparations using a method kindly provided ahead of publication by O. Resnekov (Resnekov et al 1996), as detailed below. Purified proteins were dialysed against phosphate buffered saline (PBS) overnight at 4 ЊC before cross-linking to washed Affi-Gel 10 resin (BioRad).…”
Section: Affinity Purification Of Antibodies and Commercial Antibody mentioning
confidence: 99%
“…K is synthesized as an inactive precursor, pro-K , that associates with membranes in cells (13)(14)(15). SpoIVFB is believed to be an I-Clip that processes pro-K to K on the basis of the following: a B. subtilis spoIVFB mutant is defective in processing (14), coexpression of spoIVFB and sigK (encoding pro-K ) in growing B. subtilis allows processing (16,17), SpoIVFB is a membrane protein (18) with sequence similarity to the S2P family of I-Clips (4,5,19), and mutational analysis of conserved motifs in apparent transmembrane segments of SpoIVFB supports the idea that it is a metalloprotease (4,5). However, as is the case for all I-Clips, cleavage of a physiological substrate in vitro with purified enzyme has not been accomplished.…”
mentioning
confidence: 99%
“…SpoIVFB forms a complex with SpoIVFA and BofA in the outer forespore membrane (OFM) (Fig. 1) (18,20). This (21).…”
mentioning
confidence: 99%